Research progress of ferroptosis in Parkinson’s disease: a bibliometric and visual analysis - Lu, Yangguang; Chen, Yiqun; Jiang, Zihan; Ge, Yaoying; Yao, Ruotong; Geng, Shangze; Zhang, Jinxiu; Chen, Feng; Wang, Yukai; Chen, Guangyong; Yang, Dehao (Frontiers in Aging Neuroscience, 2023)
Background: In recent years, the role of ferroptosis in Parkinson's disease (PD) has become a research hotspot based on evidence of abnormal iron deposition and lipid peroxidation damage in the brains of PD patients. This study aims to examine the relevant research on ferroptosis and PD from a bibliometric perspective.Methods: Original research and review articles related to ferroptosis and PD were retrieved from the Web of Science Core Collection (WOSCC) database. Statistical analysis and visualization of information including countries, institutions, authors, journals, and keywords of the included studies were conducted using the R software package "bibliometrix".Results: A total of 390 articles met the inclusion criteria, averaging 35.69 citations per article. From 2012 to 2022, the average annual growth rate of research in this area was 64.26%. The corresponding authors of published articles were mainly affiliated with institutions in China, the United States, and This is a provisional file, not the final typeset article Australia. Shanghai Jiao Tong University in China and the University of Melbourne in Australia emerged as the most active and influential institutions. The journal with the highest H-index and publication output was Free Radical Biology and Medicine. "Ferroptosis ", "immunotherapy", "prognosis" and "microenvironment" were identified as high-frequency keywords, indicating current and future research directions in this field.Conclusion: This bibliometric study provides insights into current research hotspots and emerging trends in the growing field of ferroptosis research related to PD. The high-frequency keywords identified highlight active areas of investigation involving methods, mechanisms, and populations of interest.